2005
DOI: 10.1073/pnas.0505513102
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring disease progression in transgenic mouse models of Alzheimer's disease with proton magnetic resonance spectroscopy

Abstract: Currently no definitive biomarker of Alzheimer's disease (AD) is available, and this impedes both clinical diagnosis in humans and drug discovery in transgenic animal models. Proton magnetic resonance spectroscopy ( 1 H MRS) provides a noninvasive way to investigate in vivo neurochemical abnormalities. Each observable metabolite can potentially provide information about unique in vivo pathological processes at the molecular or cellular level. In this study, the age-dependent 1 H MRS profile of transgenic AD mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
182
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(218 citation statements)
references
References 31 publications
(38 reference statements)
25
182
4
Order By: Relevance
“…Dedeoglu et al (2004) but not Marjanska et al (2005) reproduced these findings in mice possessing only the mutated APP gene. Both authors reported, however, higher cerebral taurine to creatine ratio in the brain of APP transgenic mice compared to wild type mice (Dedeoglu et al, 2004;Marjanska et al, 2005). These results were confirmed by in vitro NMR spectroscopy of brain extracts, in which glutathione levels were additionally found to be lower than in controls (Dedeoglu et al, 2004).…”
Section: Alzheimer's Diseasesupporting
confidence: 71%
See 2 more Smart Citations
“…Dedeoglu et al (2004) but not Marjanska et al (2005) reproduced these findings in mice possessing only the mutated APP gene. Both authors reported, however, higher cerebral taurine to creatine ratio in the brain of APP transgenic mice compared to wild type mice (Dedeoglu et al, 2004;Marjanska et al, 2005). These results were confirmed by in vitro NMR spectroscopy of brain extracts, in which glutathione levels were additionally found to be lower than in controls (Dedeoglu et al, 2004).…”
Section: Alzheimer's Diseasesupporting
confidence: 71%
“…Additionally, it was found that once amyloid plaques are observed, NAA levels are inversely associated to the area of cortex occupied by plaques (Choi et al, 2010). Dedeoglu et al (2004) but not Marjanska et al (2005) reproduced these findings in mice possessing only the mutated APP gene. Both authors reported, however, higher cerebral taurine to creatine ratio in the brain of APP transgenic mice compared to wild type mice (Dedeoglu et al, 2004;Marjanska et al, 2005).…”
Section: Alzheimer's Diseasesupporting
confidence: 56%
See 1 more Smart Citation
“…MRS thus can report about neurotransmitters (glutamate, aspartate and gaminobutyric acid), bioenergetic metabolites (creatines (Cre), lactic acid (Lac)) and osmolytes (N-acetyl-asparate (NAA)), molecules involved with membrane synthesis (cholines (Cho)), sugars (glucose, inositols) and other CNS metabolites present at millimolar concentrations 14,15 . MRS has afforded valuable insights into the nature of disease metabolism [16][17][18] ; furthermore, since some of these metabolites are selectively compartmentalized, for example, NAA is considered intraneuronal, whereas myo-inositols reside mostly in astrocytes, MRS can potentially resolve structurally distinct cellular environs.…”
mentioning
confidence: 99%
“…Despite the practical challenges in performing MRS studies in living mice [see refs (82)(83)(84) for reviews], several groups have shown the feasibility of performing spectroscopic assessments in a routine manner. Areas of application in mice include neurosciences (85)(86)(87), cardiac (88) and musculoskeletal diseases (89,90), and cancer (91)(92)(93)(94). The use of high field strengths (9.4 T) in conjunction with advanced shim capabilities has allowed the acquisition of high-resolution proton spectra from the mouse brain (95,96).…”
Section: Mri and Mrsmentioning
confidence: 99%